Strengthening Democracy in Indonesia: Comparison between Representative and Direct Presidential Election Policies - Boy Anugerah (Jurnal Studi Sosial dan Politik, 2022)
The direct presidential election policy was implemented in Indonesia for the first time in 2004 as a result of the third amendment to the constitution in 2001, and it continued in the next presidential elections. This kind of election has replaced the old representative presidential election policy. However, since the implementation in 2004, there have been many criticisms from several parties. These parties consider this to have negative impacts, such as black campaigns, hoaxes, hate speeches, and social gaps in society. Therefore, they propose to return the mechanism to the old policy. This article aims to analyze and compare the two presidential election policies and strive for an optimal presidential election policy to improve the quality of democracy in Indonesia. To present the results, we have reviewed secondary data mainly from the literature (journal, book, and act) and conducted in-depth interviews with scholars in the field. The main finding is that the direct presidential election policy is proven to improve the quality of democracy by fulfilling the three main aspects of the Indonesia Democracy Index (IDI). Nevertheless, to make it better, some improvements are needed as follows: reforming political parties, implementing the convention system, removing the presidential threshold, providing an independent channel to become a candidate, strengthening the responsibility and integrity of state officials in law enforcement, and regulating all negative impacts in binding regulations